Frozen shoulder: a narrative review of current treatment concepts and the underlying scientific evidence - 김준영; Gahlot Nitesh; 박형빈 (Clinics in shoulder and elbow, 2025)
Frozen shoulder (FS) is a challenging disorder defined by persistent shoulder pain and progressively reduced joint motion. Despite its clinical significance, the underlying pathophysiology remains incompletely understood, posing challenges to optimal management. This review examines current treatment strategies, encompassing conservative approaches as well as procedural options. Evidence comparing the outcomes, complications, and recovery profiles of these techniques is critically analyzed to guide decision-making based on patient-specific factors and disease stage. Furthermore, recent advancements in understanding the molecular mechanisms of FS and the potential for novel therapeutic approaches are discussed. This comprehensive review underscores the importance of tailored treatment strategies and calls for further high-quality research to address persistent knowledge gaps in managing FS. KCI Citation Count: 0